The Genetics Revolution: History, Fears, and Future of a Life-Altering Science - Rose M Morgan (Greenwood Press, 2006)
What will our lives be like fifty years from now? What will we know about ourselves as humans, and how will that affect our lives? It's impossible to know the future for certain, but one thing we do know-perhaps nothing will alter our future more than the Genetics Revolution of the past thirty-five years. This book clarifies the history and examines the possible impact of five major areas of genetic research: The Human Genome Project and genetic engineering, In vitro fertilization (IVF) and the technology of reproduction, The Human Genome Diversity Project, which is studying the variation of the human genome, Embryonic stem-cell research, Cloning. All of these areas of research produce two reactions among the general public-hope for the improvement of people's lives, and fear of science out of control. The Genetics Revolution examines the scientific, social, and political impacts of the genetics on everyday life-in the past, in the present, and in the future. Each specific topic is contained within its own chapter for ease in accessing specific information. This is an ideal resource for students, teachers, and others preparing research papers. In addition, it integrates science and social science topics in a way that supports topics in the school curricula. The book contains documented, current information that both supports and challenges current thinking about genetics.